(untitled) (Veterinary Science, 2018)
Magnetic nanoparticles (MNPs) based on magnetite (Fe3O4) coated with silica find various applications in the field of biomedical nanotechnology, due to their stability in aqueous medium. However, the inertia of the silica in terms of its reactivity limits the incorporation of specific functionalizers such as drugs and other ligands of interest. The challenge of this work focuses on obtaining biocompatible MNPs coated with silica and gelatin as theranostic agents in various biomedical fields, including veterinary medicine. Photodynamic therapy represents an alternative and a complement to chemo and radiotherapy, conventional tools for the treatment of different pathologies such as oncology. It consists of the use of photosensitive molecules that, when activated with light of a certain wavelength, transfer their excess of energy to neighboring oxygen molecules. This phenomenon generates reactive oxygen species toxic to cells. Thus, the incorporation of a photosensitive agent to the magnetic silica nanoparticles functionalized with gelatin would facilitate their specific transport to the affected cells from the effect of an external magnetic field. This would result in a functional theranostic both for the diagnosis (by MRI) and for the treatment (phototherapy). In this work, various experimental conditions were explored from MNPs of magnetite coated with citric acid and silica for the deposition of gelatin from the co-precipitation method. An optimum formulation was obtained that was characterized integrally from the physicochemical point of view. As a photosensitive molecule, methylene blue was selected and two routes were explored for its incorporation into MNPs: 1-simple adsorption for 24 hours and 2-encapsulation. The evaluation of both procedures revealed the successful incorporation of the photosensitive agent, obtaining magnetic nanosystems with potential theranostic properties applicable in the veterinary field.